93.4k views
0 votes
Solve the system of equations by the substitution method.
6x - y = 27
5x + 3y = 11

User CornPuff
by
4.8k points

2 Answers

3 votes

x=4. y=-3

Explanation:

from equation 2

5x+3y=11..,.........2

3y=11-5x

y=11-5x/3............3

subtitute the value of y into equation 1

6x-y=27

6x-(11-5x)/3=27

6x-11+5x/3=27

lcm =3

multiplying through by 3

3(6x)-11+5x=3(27)

18x-11+5x=81

18x+5x=81+11

23x=92

x=4

when x= 4

subtitute x into equation 3

y=11-5(4)/3

y=11-20/3

y=-9/3

y=-3

x,y= 4&-3

User NtgCleaner
by
4.8k points
2 votes

Answer:

all work is shown and pictured

Solve the system of equations by the substitution method. 6x - y = 27 5x + 3y = 11-example-1
User Sushant Mehta
by
4.7k points